PERBANDINGAN PANDANGAN HUKUM PENGADILAN TINGGI SAMARINDA DAN MAHKAMAH AGUNG DALAM PERKARA CITIZEN LAWSUIT - Effendi, Evi Nur Rokhmah (Verstek, 2022)
This article aims to determine the legal view of the Judge of the Samarinda High Court in upholding the decision of the Samarinda District Court Judge in the Citizen Lawsuit case. In addition, to find out the legal views of the Supreme Court Judges in canceling the decision of the Samarinda High Court Judge on the Citizen Lawsuit case. This research article is a normative legal research with a case approach. This legal research is descriptive. The types of legal materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials in this research article is literature study and analyzed using the syllogism method which uses deductive thinking patterns. Based on this research article, it is found that there are 2 differences in the perspectives of the Samarinda High Court Judges and the Supreme Court Judges. The Samarinda High Court Judge in his perspective stated that the lawsuit filed was a Citizen Lawsuit because it had been recognized in Indonesian judicial practice. The notification or subpoena submitted is in accordance with the provisions of the Decree of the Chief Justice of the Republic of Indonesia Number: 36/KMA/SK/II/2013. Meanwhile, the Supreme Court Judge in his perspective stated that the lawsuit could not be accepted or Niet Ontvankelijke Verklaard (NO) and the notification or summons did not meet the requirements because there were parties in the case who were withdrawn as Defendants without being notified.